2012
DOI: 10.1007/s00436-012-2910-1
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne viruses in Europe

Abstract: The aim of this review is to present briefly background information on 27 tick-borne viruses ("tiboviruses") that have been detected in Europe, viz flaviviruses tick-borne encephalitis (TBEV), louping-ill (LIV), Tyuleniy (TYUV), and Meaban (MEAV); orthobunyaviruses Bahig (BAHV) and Matruh (MTRV); phleboviruses Grand Arbaud (GAV), Ponteves (PTVV), Uukuniemi (UUKV), Zaliv Terpeniya (ZTV), and St. Abb's Head (SAHV); nairoviruses Soldado (SOLV), Puffin Island (PIV), Avalon (AVAV), Clo Mor (CMV), Crimean-Congo hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
133
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(144 citation statements)
references
References 110 publications
2
133
0
9
Order By: Relevance
“…These viruses had been characterized only to a limited extent using biological and serological methods (i.e., electron microscopy, neutralization test, and complement fixation test) before the introduction of molecular biological techniques. Our RT-PCR results have confirmed that two strains of UUKV (Potepli 63 and SCOT FT 254 [34]), which were classified as UUKVs serologically, are phleboviruses. The RT-PCR results have also identified Kismayo virus, Kaisodi virus, Silverwater virus, and Lanjan virus as likely phleboviruses (Fig.…”
Section: Resultssupporting
confidence: 73%
“…These viruses had been characterized only to a limited extent using biological and serological methods (i.e., electron microscopy, neutralization test, and complement fixation test) before the introduction of molecular biological techniques. Our RT-PCR results have confirmed that two strains of UUKV (Potepli 63 and SCOT FT 254 [34]), which were classified as UUKVs serologically, are phleboviruses. The RT-PCR results have also identified Kismayo virus, Kaisodi virus, Silverwater virus, and Lanjan virus as likely phleboviruses (Fig.…”
Section: Resultssupporting
confidence: 73%
“…The most important European tick-borne viruses from public health perspective are Crimean-Congo haemorrhagic fever virus (CCHFV) and TBEV (Hubalek and Rudolf 2012). The dynamics of TBE has been studied extensively in the last decades (Amicizia et al 2013;Jaenson et al 2012).…”
Section: Emerging Tick-borne Pathogens In Europementioning
confidence: 99%
“…BHAV was isolated in India in 1954 from a tick on a paralyzed goat and causes fever and signs of central nervous system involvement in young ruminants but not in adult animals. A few cases of febrile illness in humans have been described, and serological surveys in Eastern Europe suggest that BHAV is endemic in that region and may cause undetected human infection (6,25). Two recent papers report nucleotide sequence determination of Bhanja group viruses (26,27) and show that they are related to SFTSV and HRTV.…”
mentioning
confidence: 99%